Perancangan Sistem Pendukung Keputusan Pengujian dan Sertifikasi Mutu Barang Hasil Perkebunan Dengan Metode Fuzzy Mamdani - Simorangkir, Srihartati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Plantation products are goods obtained from the results of planting activities - planting in the soil or other media by following a number of scientific procedures to meet the needs of the community. Quality testing and certification of plantation products is absolutely necessary because these plantation products are a daily necessity. UPT. PSMB (Balai for Testing and Certification of Quality of Goods). Testing is currently carried out in a testing laboratory by collecting test data until the test report results are made manually. This of course can reduce the work efficiency of the test team because the manual system does not guarantee data accuracy, wastes money and takes a lot of time. With these problems, a computerized decision system is needed. A decision support system using the Fuzzy Mamdani method, is a decision support system that can assist in making systematic quality testing decisions. This method has tolerance for inaccurate data, can build and apply the experiences of experts directly without having to go through a training process based on natural language. With a decision support system with this method, it allows decision makers to perform computations quickly and cost-effectively. It can also overcome cognitive limitations in data processing and storage